2011
DOI: 10.3164/jcbn.11-13
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure and nutritional status in patients undergoing transthoracic esophagectomy for esophageal cancer

Abstract: This study was to assess the resting energy expenditure of patients with esophageal cancer using indirect calorimetry. Eight male patients with esophageal cancer and eight male healthy controls were enrolled in this study. All patients underwent transthoracic esophagectomy with lymph nodes dissections. The resting energy expenditure was measured preoperatively, and on postoperative day 7 and 14 using indirect calorimetry. Preoperatively, the measured resting energy expenditure/body weight in these patients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…When the influence of the perioperative time (preoperative or day 7 or 14 after the procedure) on the energy metabolism of these patients was evaluated, a significant increase in REE was observed on postoperative day 7. However, after 14 days, the values approached those recorded initially 31 . Our results also showed that the pre‐ and postoperative REE values were similar, suggesting that there was no interference of the surgical procedure with the results.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…When the influence of the perioperative time (preoperative or day 7 or 14 after the procedure) on the energy metabolism of these patients was evaluated, a significant increase in REE was observed on postoperative day 7. However, after 14 days, the values approached those recorded initially 31 . Our results also showed that the pre‐ and postoperative REE values were similar, suggesting that there was no interference of the surgical procedure with the results.…”
Section: Discussionsupporting
confidence: 76%
“…This finding demonstrates that closely matched controls were used in this work, as differences in relation to FFM 12 or weight and BMI 11 between cases and controls may result in differences concerning energy expenditure. Other authors have also suggested that the REE of patients and controls is similar 11 , 12 , 24 , 28 , 31 . However, Scott and colleagues (2001) evaluated patients with lung cancer and showed that the REE of patients was lower than that of controls 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that BEE of patients with squamous cell carcinoma was underestimated when using the HBE [62]. However, current evidence is inconsistent, since some studies suggest that REE is normal and is not affected by stage of disease [63][64][65]. Consequently, more research should be conducted in order to shed light on this controversial field.…”
Section: Mechanisms Of Malnutritionmentioning
confidence: 96%
“…REE can be unchanged, increased or decreased in relation to the predicted energy expenditure (18)(19)(20) . In about 25 % of patients with active cancer, REE measured by the gold standard method, indirect calorimetry, is more than 10 % higher, and in another 25 % it is more than 10 % lower than predicted energy expenditure (21) .…”
Section: Energy Expenditure and Physical Activitymentioning
confidence: 99%